Tracing intermolecular Coulombic decay of carbon-dioxide dimers and oxygen dimers after valence photoionization - Iskandar, W.; Gatton, A. S.; Gaire, B.; Sturm, F. P.; Larsen, K. A.; Champenois, E. G.; Shivaram, N.; Moradmand, A.; Williams, J. B.; Berry, B.; Severt, T.; Ben-Itzhak, I.; et al. (My University, 2019)
We have conducted an experimental study on the photo double ionization (PDI) of carbon-dioxide dimers at photon energies of 37 and 55 eV and oxygen dimers at photon energies of 38, 41.5, and 46 eV, while focusing on the dissociation dynamics upon single-photon absorption. The investigation was performed by applying the cold-target recoil-ion momentum spectroscopy method in order to collect and record the three-dimensional momenta of the ionic fragments and emitted electrons from the dissociating dimer in coincidence. The kinetic-energy release upon fragmentation and the electron angular distributions in the laboratory and body-fixed frames, as well as the relative electron-electron emission angle, show unambiguous experimental evidence of intermolecular Coulombic decay (ICD) in carbon-dioxide dimers upon photoionization below and above the double-ionization threshold of CO2 monomers. The PDI of oxygen dimers is less conclusive and shows contributions from ICD and knock-off ionization mechanisms. As for atomic dimers, the present results reveal that ICD in CO2 dimers after valence PDI can also serve as a source for low-energy electrons, known to be very relevant in biological systems, cells, and tissues.
Keywords: Coulombic decay; carbon-dioxide dimers; valence photoionization